Fatal Systemic Vasoconstriction in a Case of Metastatic Small-Intestinal NET - Stenzel Jochen; Noe Sebastian; Holzapfel Konstantin; Erlmeier Franziska; Eyer Florian (Case Reports in Gastrointestinal Medicine)
An increased release of serotonin secreted by ileal NETs is thought to be the major factor causing the carcinoid syndrome. However, in acutely arising carcinoid crisis also other vasoactive factors may lead to hazardous fluctuations in blood pressure and bronchial constriction. In rare cases, systemic vasoconstriction can be observed, probably caused by catecholamines or similar acting substances. Here, we report a fatal case of fulminant systemic vasoconstriction possibly caused by catecholamines in a patient with metastasized ileal NET. The vasospasm was detected by CT-angiography, and hemodynamic monitoring revealed a high systemic vascular resistance. Epinephrine, norepinephrine, and chromogranin A levels in plasma were elevated as was the urinary 5-hydroxyindoleacetic acid (5-HIAA). The cause of death was heart failure due to severe circulatory insufficiency. The progression of the tumor disease was confirmed by autopsy.